Assessment of health-related quality of life in individuals with depressive symptoms: validity and responsiveness of the EQ-5D-3L and the SF-6D - Maike Stolz; Christian Albus; Manfred E. Beutel; Hans-Christian Deter; Kurt Fritzsche; Christoph Herrmann-Lingen; Matthias Michal; Katja Petrowski; Joram Ronel; Jobst-Hendrik Schultz; Wolfgang Söllner; Cora Weber; et al. (The European Journal of Health Economics, 2022)
AbstractBackgroundThe EQ-5D and the SF-6D are examples of commonly used generic preference-based instruments for assessing health-related quality of life (HRQoL). However, their suitability for mental disorders has been repeatedly questioned.ObjectiveTo assess the responsiveness and convergent validity of the EQ-5D-3L and SF-6D in patients with depressive symptoms.MethodsThe data analyzed were from cardiac patients with depressive symptoms and were collected as part of the SPIRR-CAD (Stepwise Psychotherapy Intervention for Reducing Risk in Coronary Artery Disease) trial. The EQ-5D-3L and SF-6D were compared with the HADS (Hospital Anxiety and Depression Scale) and PHQ-9 (Patient Health Questionnaire) as disease-specific instruments. Convergent validity was assessed using Spearman's rank correlation. Effect sizes were calculated and ROC analysis was performed to determine responsiveness.ResultsData from 566 patients were analysed. The SF-6D correlated considerably better with the disease-specific instruments (|rs|=0.167em0.63–0.68) than the EQ-5D-3L (|rs|=0.167em0.51–0.56). The internal responsiveness of the SF-6D was in the upper range of a small effect (ES: -~0.44 and -~0.47), while no effect could be determined for the EQ-5D-3L. Neither the SF-6D nor the EQ-5D-3L showed acceptable external responsiveness for classifying patients' depressive symptoms as improved or not improved. The ability to detect patients whose condition has deteriorated was only acceptable for the EQ-5D-3L.ConclusionOverall, both the convergent validity and responsiveness of the SF-6D are better than those of the EQ-5D-3L in patients with depressive symptoms. The SF-6D appears, therefore, more recommendable for use in studies to evaluate interventions for this population.
Keywords: I100; 610; EQ-5D-3L; SF-6D; Mental disorder; Validity; Responsiveness